A composite hard carbon material and its preparation method and application

By introducing doping active sites and multi-stage pore structures into the hard carbon anode material of sodium ion batteries and coating hard carbon particles with a soft carbon layer, the problems of slow diffusion of sodium ions and poor battery performance in sodium ion batteries are solved. , achieving efficient sodium ion storage and battery performance improvement.

CN115911320BActive Publication Date: 2025-01-14SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211464208.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-01-14
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The existing hard carbon anode materials of sodium ion batteries have problems such as unfixed chemical composition, single microstructure, and slow diffusion kinetics of sodium ion, resulting in poor battery rate performance and short cycle life.

Method used

Using composite hard carbon materials, the hard carbon particle matrix contains dispersed doping active sites and multi-stage pores. The soft carbon layer covers the surface of the hard carbon particle matrix to form a semi-enclosed pore structure, and doped carbonization through segmented calcination and multi-stage pore structure design to improve diffusion kinetics and storage capacity of sodium ions.

Benefits of technology

It improves the rate performance and power density of sodium ion batteries, extends the cycle life of the battery, improves the first Coulomb efficiency and specific capacity, is suitable for mass production, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115911320B_ABST
    Figure CN115911320B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite hard carbon material and a preparation method and application thereof. The composite hard carbon material according to the present invention comprises a hard carbon particle matrix and a soft carbon layer. The hard carbon particle matrix is ​​dispersed with doping active sites and pores, one end of the pores extends to the interior of the hard carbon particle matrix, and the other end is distributed on the surface of the hard carbon particle matrix to form an opening; the soft carbon layer is coated on the surface of the hard carbon particle matrix to cover the opening. When the composite hard carbon material is used for the negative electrode of a sodium ion battery, it has a fixed chemical composition, and can improve the diffusion kinetics and storage capacity of sodium ions in the hard carbon in the battery, thereby improving the rate performance and power density of the sodium ion battery. The present invention also provides a preparation method and application of the composite hard carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a composite hard carbon material and a preparation method and application thereof. Background Art

[0002] As lithium-ion batteries are widely used in various electronic products such as electric vehicles, mobile phones, computers, etc., the demand for lithium is increasing year by year. However, the global lithium storage capacity is extremely limited, unevenly distributed, and costly, which seriously restricts the development of low-cost, high-performance energy storage devices. Sodium and lithium are elements of the same family. Sodium has similar electrochemical properties to lithium, and has abundant reserves and low costs. Therefore, sodium-ion batteries are the next generation of commercially applicable secondary batteries after lithium-ion batteries.

[0003] Common sodium-ion batteries use hard carbon materials, transition metals and their alloy compounds as negative electrodes, and polyanions, Prussian blue, oxides and other materials as positive electrodes.

[0004] At present, the preparation of hard carbon negative electrode materials for sodium ion batteries mainly uses biomass such as coconut shells, straw, pollen, and bamboo as precursors. Specifically, biomass is used as a carbon source, and hard carbon materials are obtained as negative electrode materials for sodium ion batteries through steps such as washing, burning, oxidation, and secondary sintering. Due to the lack of qualitative analysis of raw materials, raw materials from different sources may have differences in chemical composition, and the chemical composition of raw materials is not fixed, which makes it difficult to achieve stable large-scale mass production, and the subsequent impurity removal process is also relatively complicated. In addition, in the related art, although some scholars have used hard carbon precursors with fixed chemical compositions such as glucose and phenolic resin, the prepared hard carbon materials have a single microstructure and cannot achieve high reversible storage of sodium ions. In addition, the diffusion kinetics of sodium ions in this type of hard carbon are slow, that is, the ion transmission path is long and the transmission speed is slow, resulting in poor rate performance of the assembled battery, short cycle life, and low first coulomb efficiency.

[0005] In summary, it is still necessary to develop a new hard carbon material suitable for sodium ion battery negative electrode and a corresponding preparation method to solve the problems existing in the hard carbon negative electrode materials of sodium ion batteries. Summary of the invention

[0006] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a composite hard carbon material, which has a fixed chemical composition when used as a negative electrode of a sodium ion battery, and can improve the diffusion kinetics and storage capacity of sodium ions in the hard carbon in the battery, thereby improving the rate performance and power density of the sodium ion battery.

[0007] The invention also provides a method for preparing the composite hard carbon material.

[0008] The invention also provides a negative electrode material for a sodium ion battery.

[0009] The invention also provides a sodium ion battery.

[0010] A first aspect of the present invention provides a composite hard carbon material, the composite hard carbon material comprising:

[0011] A hard carbon particle matrix, wherein the hard carbon particle matrix includes dispersed doping active sites and pores, one end of the pores extending into the interior of the hard carbon particle matrix and the other end of the pores being distributed on the surface of the hard carbon particle matrix to form an opening;

[0012] The soft carbon layer is coated on the surface of the hard carbon particle matrix and covers the opening.

[0013] One of the technical solutions of the present invention regarding the composite hard carbon material has at least the following beneficial effects:

[0014] In the composite hard carbon material of the present invention, the hard carbon particle matrix contains dispersed doping active sites and pores, one end of the pores extends into the hard carbon particle matrix, and the other end of the pores is distributed on the surface of the hard carbon particle matrix to form an opening, and the soft carbon layer is coated on the surface of the hard carbon particle matrix to cover the opening, so that the pores have a semi-closed structure. When used as a negative electrode material for a sodium ion battery, since the doping active sites are dispersed in the hard carbon particle matrix, the semi-closed structure of the pores and doping active sites can simultaneously increase the platform area capacity and slope area capacity of the composite hard carbon negative electrode material, while improving the overall capacity, it also ensures the excellent rate performance of the sodium ion battery.

[0015] In the composite hard carbon material of the present invention, a pore structure is dispersed in the hard carbon particle matrix. When used as the negative electrode of a sodium ion battery, reversible storage of sodium can be achieved during the charging process. After sodium ions migrate to the interface of the hard carbon negative electrode, they are stored in the pores in the form of sodium clusters. At the same time, doping active sites are also dispersed in the hard carbon particle matrix, which can improve the diffusion kinetics and storage capacity of sodium ions in the battery, and improve the rate performance and power density of the sodium ion battery.

[0016] According to some embodiments of the present invention, the doped active sites include at least one of nitrogen doped active sites, phosphorus doped active sites, sulfur doped active sites, oxygen doped active sites and boron doped active sites.

[0017] According to some embodiments of the present invention, the pores have a pore diameter ranging from 0.6 nm to 5 μm.

[0018] The pore size ranges from 0.6nm to 5μm, and the pore size distribution range is wide. Therefore, the pores are multi-level micro-nano pores, including both nano-scale pores and micro-scale pores. When used as the negative electrode of a sodium ion battery, reversible storage of sodium can be achieved during the charging process. After sodium ions migrate to the interface of the hard carbon negative electrode, they can be stored in these micro-nano pores in the form of sodium clusters.

[0019] According to some embodiments of the present invention, the pores have a pore diameter ranging from 1 nm to 5 μm.

[0020] According to some embodiments of the present invention, the pores have a pore size ranging from 1 μm to 5 μm.

[0021] According to some embodiments of the present invention, the raw materials for preparing the composite hard carbon material include a hard carbon precursor, a dispersant, a doping precursor, a pore former and a soft carbon precursor.

[0022] The role of the hard carbon precursor is to provide a hard carbon particle matrix.

[0023] The function of the dispersant is to facilitate the preparation by first dispersing the hard carbon precursor in the dispersant.

[0024] The role of the doping precursor is to provide doping active sites.

[0025] The role of the pore former is to facilitate the generation of pores with a wide range of pore size distribution, that is, multi-level pores, during the preparation process. For sodium-ion batteries, the multi-level pore structure further helps to store sodium in the form of sodium clusters.

[0026] The role of the soft carbon precursor is to achieve the coating of hard carbon, reduce the decomposition of electrolyte on the surface of porous hard carbon negative electrode, and thus improve the first coulombic efficiency of the battery.

[0027] According to some embodiments of the present invention, the addition amount of the soft carbon precursor is 20% to 400% of the hard carbon precursor in terms of mass percentage.

[0028] According to some embodiments of the present invention, the hard carbon precursor includes at least one of a triazole precursor, a resin precursor, sugar, starch, gelatin, phloroglucinol and an aniline precursor.

[0029] According to some embodiments of the present invention, the triazole precursor includes melamine.

[0030] According to some embodiments of the present invention, the resin precursor includes at least one of phenolic resin, phenolic epoxy resin, phenol-furfural resin, phenol-formaldehyde resin, m-diphenol-formaldehyde resin, p-diphenol-formaldehyde resin, PVP, polyacrylonitrile resin, polyvinylidene fluoride resin and polyvinyl chloride resin.

[0031] According to some embodiments of the present invention, the aniline precursor includes at least one of polyaniline and polydopamine.

[0032] According to some embodiments of the invention, the sugar comprises at least one of sucrose, glucose, chitin, chitosan and cellulose.

[0033] According to some embodiments of the present invention, melamine is a preferred hard carbon precursor.

[0034] According to some embodiments of the present invention, the dispersant includes at least one of ethanol, methanol, ether, acetone, benzene, toluene, chlorobenzene, styrene and tetrahydrofuran.

[0035] According to some embodiments of the present invention, the doping precursor includes at least one of a phosphorus-containing precursor, a sulfur-containing precursor, and a nitrogen-containing precursor.

[0036] According to some embodiments of the present invention, the phosphorus-containing precursor includes at least one of an organic phosphorus-based precursor and an inorganic phosphorus-based precursor.

[0037] According to some embodiments of the present invention, the organophosphorus precursor includes phytic acid or triphenylphosphine.

[0038] According to some embodiments of the present invention, the inorganic phosphorus-based precursor includes at least one of sodium hypophosphite, phosphorus pentoxide, phosphoric acid, red phosphorus and white phosphorus.

[0039] According to some embodiments of the present invention, the sulfur-containing precursor includes at least one of ammonium persulfate, sulfuric acid, thiourea, sublimated sulfur, sulfur powder, zinc sulfate, calcium sulfate, magnesium sulfate, sulfurous acid, hydrogen sulfide, zinc persulfate, magnesium persulfate, calcium persulfate, thiol and thioether.

[0040] According to some embodiments of the present invention, the nitrogen-containing precursor includes at least one of ammonia, urea, cyanamide, dicyandiamide, polypyrrole, aniline, nitric acid and nitrous acid.

[0041] According to some embodiments of the present invention, phosphoric acid is a preferred doping precursor.

[0042] According to some embodiments of the present invention, the pore former includes at least one of a chemical pore former and a physical pore former.

[0043] According to some embodiments of the invention, chemical pore formers include acids, bases and salts.

[0044] According to some embodiments of the present invention, in the pore former, the acid comprises phosphoric acid.

[0045] According to some embodiments of the present invention, in the pore-forming agent, the base includes at least one of sodium hydroxide, potassium hydroxide, lithium hydroxide and calcium hydroxide.

[0046] According to some embodiments of the present invention, in the pore-forming agent, the salt includes at least one of potassium sulfide, potassium dihydrogen phosphate, zinc chloride, calcium chloride and potassium carbonate.

[0047] According to some embodiments of the invention, the physical pore former comprises at least one of carbon dioxide and water vapor.

[0048] According to some embodiments of the present invention, potassium hydroxide is the preferred pore former.

[0049] According to some embodiments of the present invention, the soft carbon precursor includes at least one of a petrochemical soft carbon precursor and a coal chemical soft carbon precursor.

[0050] According to some embodiments of the present invention, the petrochemical soft carbon precursor includes at least one of mesophase pitch, coal tar pitch, aromatic coal pitch, medium temperature pitch, USP low temperature pitch, high temperature pitch, hexaphenylbenzene, perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) and medium temperature coal tar.

[0051] According to some embodiments of the present invention, the coal chemical industry soft carbon precursor is at least one of anthracite, coke, petroleum coke, needle coke and mesocarbon microbeads (MCMB).

[0052] According to some embodiments of the present invention, mesophase pitch is a preferred soft carbon precursor.

[0053] A second aspect of the present invention provides a method for preparing the composite hard carbon material, comprising the following steps:

[0054] S1: dispersing a hard carbon precursor in a dispersant, adding a doping precursor and mixing, and evaporating to dryness to obtain a mixed system of the doping precursor and the hard carbon precursor;

[0055] S2: sintering the product of step S1 for the first time in a protective atmosphere to obtain pre-carbonized carbon;

[0056] S3: After mixing the pre-carbonized carbon with the pore-forming agent, sintering for the second time to obtain porous carbon;

[0057] S4: adding a soft carbon precursor to the porous carbon and performing a third sintering to obtain the composite hard carbon material.

[0058] A technical solution in the method for preparing the composite hard carbon material of the present invention has at least the following beneficial effects:

[0059] The method for preparing a composite hard carbon material of the present invention comprises the following steps: firstly dispersing a hard carbon precursor in a dispersant, adding a doping precursor and mixing, and evaporating to obtain a mixed system of a doping precursor and a hard carbon precursor, and then sintering the product of the previous step for the first time in a protective atmosphere to obtain pre-carbonized carbon, and then mixing the pre-carbonized carbon with a pore-forming agent and sintering for the second time to obtain porous carbon, and finally adding a soft carbon precursor to the porous carbon and sintering for the third time to obtain the composite hard carbon material. That is, the method for preparing a composite hard carbon material of the present invention comprises four steps: raw material mixing, doping pre-carbonization, calcination pore formation and soft carbon coating. Thus, through staged calcination, doping and carbonization, a multi-level secondary pore structure design and doping design of hard carbon are realized, which overcomes the shortcomings of the hard carbon negative electrode technology of sodium ion batteries, and solves the problems of low capacity, low initial coulomb efficiency, short cycle life, and poor battery rate performance caused by slow sodium ion kinetics of current sodium ion batteries.

[0060] The method for preparing a composite hard carbon material of the present invention involves an in-situ doping process, which can increase the number of sodium storage active sites of the hard carbon, and the doping sites can also accelerate the diffusion kinetics of sodium ions.

[0061] In the method for preparing a composite hard carbon material of the present invention, based on the modification principle of the composite hard carbon material, the processing temperature and time of the pre-carbonization, pore formation, and high-temperature coating steps can be optimized to achieve the transformation of the internal pores of the material from "open pores" to "closed pores", as well as the precise control of the pore size, so that the composite hard carbon material has a semi-closed multi-level pore structure. As mentioned above, "semi-closed" means that one end of the pore extends into the interior of the hard carbon particle matrix, and the other end is distributed on the surface of the hard carbon particle matrix to form an opening, and the opening is covered and closed by the soft carbon layer; "multi-level" means that the pore size range of the pore is wide, including both nano-scale pores and micro-scale pores.

[0062] According to the method for preparing composite hard carbon materials of the present invention, in-situ doping of nitrogen and phosphorus can be achieved by optimizing carbon sources and doping precursors, thereby improving doping effects, reducing process steps, and reducing production costs. Since the pore size range of the pores is 0.6nm to 5μm, and the pore size range is widely distributed, it can be seen that these pores can form a multi-level pore structure. When used as the negative electrode of a sodium ion battery, reversible storage of sodium can be achieved during the charging process. After sodium ions migrate to the interface of the hard carbon negative electrode, they can be stored in these micro-nanoscale pores in the form of sodium clusters.

[0063] In the present invention, the precursor used to prepare the composite hard carbon negative electrode material of the sodium ion battery has a wide source, low cost, and is green and environmentally friendly, and the preparation method is simple and the equipment used is single. During the operation of the battery, the multi-level secondary pores of the hard carbon negative electrode can store sodium single substance clusters, and the storage and extraction process are reversible, thereby improving the low potential platform area capacity of the hard carbon negative electrode; after medium-temperature calcination, the soft carbon is evenly coated on the surface of the hard carbon particles, realizing the transformation from "open pore" to "closed pore" inside the material, reducing the decomposition of the electrolyte on the surface of the porous hard carbon negative electrode, and at the same time acting as a buffer to reduce the volume change in the sodium ion storage / escape process; the preferred hard carbon precursor is in-situ nitrogen doped after pre-carbonization, and the doped precursor can be doped into the hard carbon after pre-carbonization, thereby increasing the number of hard carbon sodium storage active sites and accelerating the transmission kinetics of sodium ions; the hard carbon structure improves the reversible capacity, first coulomb efficiency, rate performance and cycle stability of the hard carbon negative electrode of the sodium ion battery.

[0064] The method for preparing composite hard carbon materials of the present invention does not require the use of expensive equipment and raw materials, nor does it require complex process control, and the reaction conditions are not harsh. Various raw materials are widely available, have sufficient storage capacity, are renewable and low in cost, and the produced composite hard carbon materials have high specific capacity and high first coulomb efficiency. The assembled sodium ion battery has excellent cycle performance and good rate performance. Since sodium ion batteries can replace traditional lithium ions with sodium ions in their electrolytes, the problem of limited lithium resource reserves can be alleviated, and their application is no longer restricted by lithium resources.

[0065] According to some embodiments of the present invention, in step S2, the temperature of the first sintering is 300°C to 1600°C.

[0066] According to some embodiments of the present invention, in step S2, the temperature of the first sintering is 300°C to 1000°C.

[0067] According to some embodiments of the present invention, in step S2, the first sintering time is 2 hours to 16 hours.

[0068] According to some embodiments of the present invention, in step S2, the first sintering time is 2 hours to 9 hours.

[0069] According to some embodiments of the present invention, in step S3, the temperature of the second sintering is 400°C to 1600°C.

[0070] According to some embodiments of the present invention, in step S3, the temperature of the second sintering is 400°C to 1300°C.

[0071] According to some embodiments of the present invention, in step S3, the temperature of the second sintering is 700°C to 1600°C.

[0072] According to some embodiments of the present invention, in step S3, the second sintering time is 1 hour to 14 hours.

[0073] According to some embodiments of the present invention, in step S3, the second sintering time is 1 h to 10 h.

[0074] According to some embodiments of the present invention, in step S3, the second sintering time is 1 hour to 6 hours.

[0075] According to some embodiments of the present invention, in step S3, the amount of the pore former added is 30% to 400% of the mass of the pre-carbonized carbon.

[0076] According to some embodiments of the present invention, in step S3, the amount of the pore former added is 50% to 200% of the mass of the pre-carbonized carbon.

[0077] According to some embodiments of the present invention, in step S4, the temperature of the third sintering is 600°C to 2200°C.

[0078] According to some embodiments of the present invention, in step S4, the temperature of the third sintering is 600°C to 1700°C.

[0079] According to some embodiments of the present invention, in step S4, the temperature of the third sintering is 900°C to 1700°C.

[0080] According to some embodiments of the present invention, in step S4, the temperature of the third sintering is 1300°C to 1700°C.

[0081] According to some embodiments of the present invention, in step S4, the third sintering time is 1 hour to 14 hours.

[0082] According to some embodiments of the present invention, in step S4, the third sintering time is 1 hour to 10 hours.

[0083] The third aspect of the present invention provides a sodium ion battery negative electrode material, comprising the composite hard carbon material.

[0084] A technical solution in the present invention regarding the negative electrode material for sodium ion batteries has at least the following beneficial effects:

[0085] The sodium ion battery negative electrode material of the present invention includes the composite hard carbon material, thereby having all the technical effects of the composite hard carbon material. Specifically, in the composite hard carbon material of the present invention, doped active sites and pores are dispersed in the hard carbon particle matrix, one end of the pores extends to the inside of the hard carbon particle matrix, and the other end of the pores is distributed on the surface of the hard carbon particle matrix to form an opening, and the soft carbon layer is coated on the surface of the hard carbon particle matrix to cover the opening, thereby the pores have a semi-closed structure. When used as a sodium ion battery negative electrode material, since doped active sites are dispersed in the hard carbon particle matrix, the semi-closed structure of the pores and doped active sites can simultaneously increase the platform area capacity and slope area capacity of the composite hard carbon negative electrode material, while improving the overall capacity, it also ensures the excellent rate performance of the sodium ion battery.

[0086] A fourth aspect of the present invention provides a sodium ion battery, comprising the sodium ion battery negative electrode material.

[0087] The technical solution of the sodium ion battery of the present invention has at least the following beneficial effects:

[0088] The sodium ion battery of the present invention uses the sodium ion battery negative electrode material of the present invention, and the sodium ion battery negative electrode material is prepared from the composite hard carbon material of the present invention, thus having all the technical effects of the composite hard carbon material. Specifically, the sodium ion battery of the present invention can achieve an initial coulombic efficiency of more than 90%, and has a high energy density, good cycle stability, and a high safety factor.

[0089] In addition, in the sodium ion battery of the present invention, the raw materials used to prepare the composite hard carbon material are extensive, low-priced, will not cause pollution to the environment, and the preparation process is simple, suitable for mass production, in line with the sustainable development strategy, and can be widely used in electric vehicles, power tools, energy storage and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 It is a schematic structural diagram of the composite hard carbon material of the present invention.

[0091] Figure 2 It is a schematic diagram of the cross-sectional structure of the composite hard carbon material of the present invention.

[0092] Figure 3 This is a microscopic morphology image of the composite hard carbon material prepared in Example 1 magnified 370 times.

[0093] Figure 4 This is a microscopic morphology image of the composite hard carbon material prepared in Example 1 magnified 4900 times.

[0094] Figure 5 This is the XRD test result of the composite hard carbon material prepared in Example 1.

[0095] Figure 6 This is the constant current charge and discharge curve when the composite hard carbon material prepared in Example 1 is used as the negative electrode of a sodium ion battery.

[0096] Figure 7 This is the long cycle curve when the composite hard carbon material prepared in Example 1 is used as the negative electrode of a sodium ion battery.

[0097] Reference numerals:

[0098] 1: hard carbon particle matrix;

[0099] 2: soft carbon layer;

[0100] 3: Active site;

[0101] 4: Holes. DETAILED DESCRIPTION

[0102] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0103] Figure 1 It is a schematic structural diagram of the composite hard carbon material of the present invention. Figure 2 is a cross-sectional view of the composite hard carbon material of the present invention. Figure 1 and Figure 2 As shown, in some embodiments of the present invention, the present invention provides a composite hard carbon material, which includes a hard carbon particle matrix 1 and a soft carbon layer 2, wherein doping active sites 3 and pores 4 are dispersed in the hard carbon particle matrix 1, one end of the pore 4 extends to the interior of the hard carbon particle matrix 1, and the other end is distributed on the surface of the hard carbon particle matrix 1 to form an opening; the soft carbon layer 2 is coated on the surface of the hard carbon particle matrix 1 to cover the opening.

[0104] It can be understood that in the composite hard carbon material of the present invention, doped active sites and pores are dispersed in the hard carbon particle matrix, one end of the pore extends to the inside of the hard carbon particle matrix, and the other end of the pore is distributed on the surface of the hard carbon particle matrix to form an opening, and the soft carbon layer is coated on the surface of the hard carbon particle matrix to cover the opening, so that the pore has a semi-closed structure. When used as a negative electrode material for a sodium ion battery, since doped active sites are dispersed in the hard carbon particle matrix, the semi-closed structure of the pores and doped active sites can simultaneously increase the platform area capacity and slope area capacity of the composite hard carbon negative electrode material, while improving the overall capacity, it also ensures the excellent rate performance of the sodium ion battery.

[0105] It can also be understood that in the composite hard carbon material of the present invention, a pore structure is dispersed in the hard carbon particle matrix. When used as the negative electrode of a sodium ion battery, reversible storage of sodium can be achieved during the charging process. After the sodium ions migrate to the interface of the hard carbon negative electrode, they are stored in the pores in the form of sodium clusters. At the same time, doping active sites are also dispersed in the hard carbon particle matrix, which can improve the kinetics and storage capacity of sodium ions in the battery, and improve the rate performance and power density of the sodium ion battery.

[0106] In some embodiments of the present invention, the doped active sites include at least one of nitrogen doped active sites, phosphorus doped active sites, sulfur doped active sites, oxygen doped active sites, and boron doped active sites.

[0107] In some embodiments of the present invention, the pore diameter ranges from 0.6 nm to 5 μm.

[0108] In some embodiments of the present invention, the pore diameter ranges from 1 nm to 5 μm.

[0109] In some embodiments of the present invention, the pore size ranges from 1 μm to 5 μm.

[0110] It should be noted that the pore size range is 0.6nm to 5μm, so the pore size distribution range is wide and the pores are multi-level micro-nano pores. When used as the negative electrode of a sodium ion battery, reversible storage of sodium can be achieved during the charging process. After sodium ions migrate to the interface of the hard carbon negative electrode, they can be stored in these micro-nano pores in the form of sodium clusters.

[0111] It can be understood that the pore size distribution is not only related to the type of pore former, but also to the process of the pore-forming step, including the calcination time, temperature, and the order of the steps. Generally speaking, the longer the sintering time and the higher the sintering temperature, the larger the pore size. However, too long sintering time and sintering temperature may have an adverse effect on the pore size distribution. For example, too high a temperature will change the structure of the carbon layer. Therefore, the pore-forming temperature of 400°C to 1600°C and the pore-forming time of 1h to 14h are relatively suitable pore-forming temperature ranges and pore-forming time ranges, that is, the temperature and time range of the second sintering.

[0112] In some embodiments of the present invention, the raw materials for preparing the composite hard carbon material include a hard carbon precursor, a dispersant, a doping precursor, a pore former and a soft carbon precursor.

[0113] It should be noted that the role of the hard carbon precursor is to provide a hard carbon particle matrix.

[0114] The function of the dispersant is to facilitate the preparation by first dispersing the hard carbon precursor in the dispersant.

[0115] The role of the doping precursor is to provide doping active sites.

[0116] The role of the pore former is to facilitate the generation of pores with a wide range of pore size distribution, i.e., multi-level pores, during the preparation process. For sodium-ion batteries, the multi-level pore structure can store sodium in the form of sodium clusters.

[0117] The role of the soft carbon precursor is to achieve the coating of hard carbon, reduce the decomposition of electrolyte on the surface of porous hard carbon negative electrode, and thus improve the first coulombic efficiency of the battery.

[0118] In some embodiments of the present invention, the amount of the soft carbon precursor added is 20% to 400% of the hard carbon precursor in terms of mass percentage.

[0119] In some embodiments of the present invention, the hard carbon precursor includes a triazole precursor, a resin precursor, sugar, starch, gelatin, phloroglucinol and an aniline precursor.

[0120] In some embodiments of the present invention, the triazole precursor includes melamine.

[0121] In some embodiments of the present invention, the resin precursor includes at least one of phenolic resin, phenolic epoxy resin, phenol-furfural resin, phenol-formaldehyde resin, m-diphenol-formaldehyde resin, p-diphenol-formaldehyde resin, PVP, polyacrylonitrile resin, polyvinylidene fluoride resin and polyvinyl chloride resin.

[0122] In some embodiments of the present invention, the aniline precursor includes at least one of polyaniline and polydopamine.

[0123] In some embodiments of the present invention, the sugar includes at least one of sucrose, glucose, chitin, chitosan, and cellulose.

[0124] In some embodiments of the present invention, melamine is the preferred hard carbon precursor.

[0125] In some embodiments of the present invention, the dispersant includes at least one of ethanol, methanol, ether, acetone, benzene, toluene, chlorobenzene, styrene and tetrahydrofuran.

[0126] In some embodiments of the present invention, the doping precursor includes at least one of a phosphorus-containing precursor, a sulfur-containing precursor, and a nitrogen-containing precursor.

[0127] In some embodiments of the present invention, the phosphorus-containing precursor includes an organic phosphorus-based precursor and an inorganic phosphorus-based precursor.

[0128] In some embodiments of the present invention, the organophosphorus precursor includes phytic acid or triphenylphosphine.

[0129] In some embodiments of the present invention, the inorganic phosphorus precursor includes at least one of sodium hypophosphite, phosphorus pentoxide, phosphoric acid, red phosphorus and white phosphorus.

[0130] In some embodiments of the present invention, the sulfur-containing precursor includes at least one of ammonium persulfate, sulfuric acid, thiourea, sublimated sulfur, sulfur powder, zinc sulfate, calcium sulfate, magnesium sulfate, sulfurous acid, hydrogen sulfide, zinc persulfate, magnesium persulfate, calcium persulfate, thiol and thioether.

[0131] In some embodiments of the present invention, the nitrogen-containing precursor includes at least one of ammonia, urea, cyanamide, dicyandiamide, polypyrrole, aniline, nitric acid and nitrous acid.

[0132] In some embodiments of the present invention, phosphoric acid is a preferred doping precursor.

[0133] In some embodiments of the present invention, the pore former includes at least one of a chemical pore former and a physical pore former.

[0134] In some embodiments of the present invention, chemical pore formers include acids, bases, and salts.

[0135] In some embodiments of the present invention, in the pore former, the acid comprises phosphoric acid.

[0136] In some embodiments of the present invention, in the pore-forming agent, the base includes at least one of sodium hydroxide, potassium hydroxide, lithium hydroxide and calcium hydroxide.

[0137] In some embodiments of the present invention, in the pore-forming agent, the salt includes at least one of potassium sulfide, potassium dihydrogen phosphate, zinc chloride, calcium chloride and potassium carbonate.

[0138] In some embodiments of the present invention, physical pore formers include carbon dioxide and water vapor.

[0139] It should be noted that when the pore former is a physical pore former, there is no need to limit the mass ratio of the pore former.

[0140] In some embodiments of the present invention, potassium hydroxide is the preferred pore former.

[0141] In some embodiments of the present invention, potassium hydroxide is the preferred pore former.

[0142] In some embodiments of the present invention, the soft carbon precursor includes at least one of a petrochemical soft carbon precursor and a coal chemical soft carbon precursor.

[0143] In some embodiments of the present invention, the petrochemical soft carbon precursor includes at least one of mesophase pitch, coal tar pitch, aromatic coal pitch, medium temperature pitch, USP low temperature pitch, high temperature pitch, hexaphenylbenzene, perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) and medium temperature coal tar.

[0144] In some embodiments of the present invention, the coal chemical industry soft carbon precursor is at least one of anthracite, coke, petroleum coke, needle coke and mesocarbon microbeads (MCMB).

[0145] Mesophase pitch is a liquid crystal phase pitch with a distinct interface generated by the heat treatment of heavy aromatic hydrocarbons, and has the characteristics of optical anisotropy. Mesophase pitch (or mesophase pitch, MP for short) is a mixture of various flat disc-shaped polycyclic aromatic hydrocarbons with a relative molecular mass of 370 to 2000, also known as liquid crystal phase pitch. Generally, substances will show optical anisotropy if they exist in a crystalline state, and optical isotropy if they exist in a liquid state; however, there is a class of substances that show an optically anisotropic turbid fluid state in the intermediate stage of the process from crystal to liquid (or reverse process), which is both in liquid form and has the optical anisotropy characteristics of crystals. It is called liquid crystal in crystallography and mesophase in phasology.

[0146] Using cheap chemical products such as perylene-3,4,9,10-tetracarboxylic dianhydride and asphalt as soft carbon precursors, the porous hard carbon particles can be uniformly coated in the medium-temperature coating stage, thereby realizing the transformation from "open pores" to "closed pores" inside the hard carbon material, inhibiting the decomposition of the electrolyte on the surface of the porous hard carbon negative electrode, and improving the first coulombic efficiency of the sodium ion battery.

[0147] In some other embodiments of the present invention, the present invention further provides a method for preparing a composite hard carbon material, comprising the following steps:

[0148] S1: dispersing a hard carbon precursor in a dispersant, adding a doping precursor and mixing, and evaporating to dryness to obtain a mixed system of the doping precursor and the hard carbon precursor;

[0149] S2: sintering the product of step S1 for the first time in a protective atmosphere to obtain pre-carbonized carbon;

[0150] S3: After mixing the pre-carbonized carbon with the pore-forming agent, sintering for the second time to obtain porous carbon;

[0151] S4: adding a soft carbon precursor to the porous carbon and performing a third sintering to obtain a composite hard carbon material.

[0152] It can be understood that the method for preparing composite hard carbon materials of the present invention is to first disperse the hard carbon precursor in a dispersant, add a doping precursor to mix, evaporate to dryness, obtain a mixed system of the doping precursor and the hard carbon precursor, and then sinter the product of the previous step for the first time in a protective atmosphere to obtain pre-carbonized carbon, then mix the pre-carbonized carbon with a pore-forming agent, and sinter for the second time to obtain porous carbon, and finally add a soft carbon precursor to the porous carbon, and sinter for the third time to obtain the composite hard carbon material. That is, the method for preparing composite hard carbon materials of the present invention includes four steps: raw material mixing, doping pre-carbonization, calcination pore formation and soft carbon coating. Thus, through staged calcination, doping and carbonization, the multi-level sub-pore structure design and doping design of hard carbon are realized, which overcomes the shortcomings of the hard carbon negative electrode technology of sodium ion batteries, and solves the current problems of low capacity, low first coulomb efficiency, short cycle life, and poor battery rate performance due to slow sodium ion kinetics.

[0153] It can also be understood that the method of preparing composite hard carbon materials of the present invention involves an in-situ doping process, which can increase the number of sodium storage active sites of the hard carbon, and the doping sites can also accelerate the diffusion kinetics of sodium ions.

[0154] It should be noted that in the method for preparing composite hard carbon materials of the present invention, based on the modification principle of composite hard carbon materials, the processing temperature and time of the pre-carbonization, pore formation, and high-temperature coating steps can be optimized to achieve the transformation of the internal pores of the material from "open pores" to "closed pores", as well as the precise control of the pore size, so that the composite hard carbon material has a semi-closed multi-level pore structure. As mentioned above, "semi-closed" means that one end of the pore extends into the interior of the hard carbon particle matrix, and the other end is distributed on the surface of the hard carbon particle matrix to form an opening, and the opening is covered and closed by the soft carbon layer; "multi-level" means that the pore size range of the pore is wide, and there are both nano-scale pores and micro-scale pores.

[0155] In addition, the method for preparing composite hard carbon materials of the present invention can also achieve in-situ doping of nitrogen and phosphorus by optimizing carbon sources and doping precursors, thereby improving doping effects, reducing process steps, and reducing production costs. Since the pore size range of the pores is 0.6nm to 5μm, and the pore size range is widely distributed, it can be seen that these pores can form a multi-level pore structure. When used as the negative electrode of a sodium ion battery, reversible storage of sodium can be achieved during the charging process. After sodium ions migrate to the interface of the hard carbon negative electrode, they can be stored in these micro-nanoscale pores in the form of sodium clusters.

[0156] It should also be noted that in the present invention, the precursor used to prepare the composite hard carbon negative electrode material of the sodium ion battery has a wide source, low cost, and is green and environmentally friendly, and the preparation method is simple and the equipment used is single. During the operation of the battery, the multi-level secondary pores of the hard carbon negative electrode can store sodium single substance clusters, and the storage and extraction process are reversible, which improves the low potential platform area capacity of the hard carbon negative electrode; after medium-temperature calcination, the soft carbon is evenly coated on the surface of the hard carbon particles, realizing the transformation from "open pore" to "closed pore" inside the material, reducing the decomposition of the electrolyte on the surface of the porous hard carbon negative electrode, and at the same time acting as a buffer to reduce the volume change of the sodium ion storage / escape process; the preferred hard carbon precursor is in-situ nitrogen doped after pre-carbonization, and the doped precursor can be doped into the hard carbon after pre-carbonization, thereby increasing the number of hard carbon sodium storage active sites and accelerating the transmission kinetics of sodium ions; the hard carbon structure improves the reversible capacity, first coulomb efficiency, rate performance and cycle stability of the hard carbon negative electrode of the sodium ion battery.

[0157] It can be understood that the method for preparing composite hard carbon materials of the present invention does not require the use of expensive equipment and raw materials, nor does it require complex process control, and the reaction conditions are not harsh. Various raw materials are widely available, have sufficient storage capacity, are renewable and low cost, and the produced composite hard carbon materials have high specific capacity and high first coulomb efficiency. The assembled sodium ion battery has excellent cycle performance and good rate performance. Since sodium ion batteries can replace traditional lithium ions with sodium ions in their electrolytes, they can alleviate the problem of limited reserves of lithium resources, so that their application is no longer restricted by lithium resources.

[0158] In some embodiments of the present invention, in step S2, the temperature of the first sintering is 300°C to 1600°C.

[0159] In some embodiments of the present invention, in step S2, the temperature of the first sintering is 300°C to 1000°C.

[0160] In some embodiments of the present invention, in step S2, the first sintering time is 2 hours to 16 hours.

[0161] In some embodiments of the present invention, in step S2, the first sintering time is 2 hours to 9 hours.

[0162] In some embodiments of the present invention, in step S3, the temperature of the second sintering is 400°C to 1600°C.

[0163] In some embodiments of the present invention, in step S3, the temperature of the second sintering is 400°C to 1300°C.

[0164] In some embodiments of the present invention, in step S3, the temperature of the second sintering is 700°C to 1600°C.

[0165] In some embodiments of the present invention, in step S3, the second sintering time is 1 hour to 14 hours.

[0166] In some embodiments of the present invention, in step S3, the second sintering time is 1 hour to 10 hours.

[0167] In some embodiments of the present invention, in step S3, the second sintering time is 1 hour to 6 hours.

[0168] In some embodiments of the present invention, in step S3, the amount of pore former added is 30% to 400% of the mass of the pre-carbonized carbon.

[0169] In some embodiments of the present invention, in step S3, the amount of the pore former added is 50% to 200% of the mass of the pre-carbonized carbon.

[0170] In some embodiments of the present invention, in step S4, the temperature of the third sintering is 600°C to 2200°C.

[0171] In some embodiments of the present invention, in step S4, the temperature of the third sintering is 600°C to 1700°C.

[0172] In some embodiments of the present invention, in step S4, the temperature of the third sintering is 900°C to 1700°C.

[0173] In some embodiments of the present invention, in step S4, the temperature of the third sintering is 1300°C to 1700°C.

[0174] In some embodiments of the present invention, in step S4, the third sintering time is 1 hour to 14 hours.

[0175] In some embodiments of the present invention, in step S4, the third sintering time is 1 hour to 10 hours.

[0176] In some other embodiments of the present invention, the present invention further provides a sodium ion battery negative electrode material, comprising the composite hard carbon material of the present invention.

[0177] It can be understood that the negative electrode material of the sodium ion battery of the present invention includes the composite hard carbon material of the present invention, and thus, it has all the technical effects of the composite hard carbon material. Specifically, in the composite hard carbon material of the present invention, doped active sites and pores are dispersed in the hard carbon particle matrix, one end of the pore extends to the inside of the hard carbon particle matrix, and the other end of the pore is distributed on the surface of the hard carbon particle matrix to form an opening, and the soft carbon layer is coated on the surface of the hard carbon particle matrix to cover the opening, so that the pore has a semi-closed structure. When used as a negative electrode material for a sodium ion battery, since doped active sites are dispersed in the hard carbon particle matrix, the semi-closed structure of the pores and doped active sites can simultaneously increase the platform area capacity and slope area capacity of the composite hard carbon negative electrode material, while improving the overall capacity, it also ensures the excellent rate performance of the sodium ion battery.

[0178] In some other embodiments of the present invention, the present invention further provides a sodium ion battery, comprising the sodium ion battery negative electrode material of the present invention.

[0179] It can be understood that the sodium ion battery of the present invention, because it uses the sodium ion battery negative electrode material of the present invention, and the sodium ion battery negative electrode material is prepared from the composite hard carbon material of the present invention, has all the technical effects of the composite hard carbon material. Specifically, the sodium ion battery of the present invention can achieve an initial coulombic efficiency of more than 90%, and has a high energy density, good cycle stability, and a high safety factor.

[0180] In addition, in the sodium ion battery of the present invention, the raw materials used to prepare the composite hard carbon material are extensive, low-priced, will not cause pollution to the environment, and the preparation process is simple, suitable for mass production, in line with the sustainable development strategy, and can be widely used in electric vehicles, power tools, energy storage and other fields.

[0181] Below, the technical solution of the present invention is better understood in conjunction with specific embodiments.

[0182] Example 1

[0183] This embodiment prepares a composite hard carbon material, which includes a hard carbon particle matrix and a soft carbon layer. The hard carbon particle matrix is ​​dispersed with doping active sites and pores, one end of the pores extends into the hard carbon particle matrix, and the other end is distributed on the surface of the hard carbon particle matrix to form an opening; the soft carbon layer is coated on the surface of the hard carbon particle matrix to cover the opening. The specific preparation method is:

[0184] S1: Disperse 10 g of hard carbon precursor melamine in 30 mL of dispersant ethanol, add 2 mL of doping precursor concentrated phosphoric acid and mix, and evaporate to dryness to obtain a mixed system of doping precursor and hard carbon precursor;

[0185] S2: sintering the product of step S1 for the first time in a tubular furnace under nitrogen conditions at a temperature of 700° C. for 5 h to obtain pre-carbonized carbon;

[0186] S3: Pre-carbonized carbon and pore-forming agent potassium hydroxide are mixed in a mass ratio of 1:1, placed in a tubular furnace, and sintered for the second time under nitrogen conditions at a temperature of 700° C. for 3 h to obtain doped porous hard carbon;

[0187] S4: Wash the doped porous hard carbon with deionized water and dry it, add 4 g of soft carbon precursor intermediate phase asphalt and grind it evenly, place it in a tubular furnace, and perform the third sintering under nitrogen conditions. The third sintering temperature is 1300°C and the time is 4 hours to obtain a composite hard carbon material.

[0188] Comparative Example 1

[0189] This comparative example prepares a composite hard carbon material, which is different from Example 1 in that the negative electrode hard carbon material of Comparative Example 1 is directly prepared by calcining melamine at 1300° C. for 4 hours without doping, pore formation and coating. See Table 1 for details.

[0190] Comparative Example 2

[0191] Comparative Example 2 is a hard carbon negative electrode material prepared using straw as a carbon source according to the preparation method of Example 3 in CN110719891A as a negative electrode for a sodium ion battery. The performance differences are specifically shown in Table 1.

[0192] The sodium metal sheet was used as the negative electrode of the battery, and the hard carbon material prepared in Example 1 and Comparative Examples 1 and 2 was used as the positive electrode of the battery. The button cell was assembled in a glove box filled with argon and with a strictly controlled water and oxygen index, and charged and discharged at a current density of 30 mA / g at a voltage of 0-2 V. The results and comparison are shown in Table 1.

[0193] Table 1 Performance comparison between Example 1 and Comparative Examples 1 and 2

[0194]

[0195] As can be seen from Table 1, compared with the hard carbon directly fired from melamine and the hard carbon negative electrode material prepared with straw as the carbon source, the composite hard carbon negative electrode material of the present invention has better specific capacity, first coulombic efficiency and cycle performance, and has a wide range of raw materials for preparation and a simple preparation process.

[0196] The microstructure of the composite hard carbon material prepared in Example 1 was tested by scanning microscopy. Figure 3 and Figure 4 shown. Figure 3 This is the microscopic morphology of the composite hard carbon material prepared in Example 1 magnified 370 times. Figure 4This is the microscopic morphology of the composite hard carbon material prepared in Example 1 magnified 4900 times. Figure 3 and Figure 4 It can be seen that in the composite hard carbon material prepared by the present invention, the hard carbon particles are wrapped by soft carbon, and obvious multi-level secondary pores are distributed on the hard carbon particles.

[0197] The composite hard carbon material prepared in Example 1 was characterized by X-ray powder diffraction. Figure 5 As shown. Figure 5 It can be seen that there are two obvious carbon peaks at 2θ=24° and 44°, corresponding to the (002) and (100) graphite planes. Compared with the pure hard carbon structure, the carbon peak width at 2θ=24° is reduced. This is the result of the overall order of the carbon material being improved due to the soft carbon coating. It is a typical XRD peak of soft and hard carbon composite.

[0198] Figure 6 1 is a constant current charge-discharge curve when the composite hard carbon material prepared in Example 1 is used as the negative electrode of a sodium ion battery. Figure 6 It can be seen that the sodium storage capacity of the composite hard carbon material "platform area" can reach 250mAh·g -1 The sodium storage capacity in the “slope phase” can reach 168 mAh g -1 , indicating that the doping sites and hierarchical pores have a practical improvement in sodium storage capacity, and have high charge and discharge reversibility and high Coulombic efficiency.

[0199] Figure 7 This is the long cycle curve when the composite hard carbon material prepared in Example 1 is used as the negative electrode of the sodium ion battery. Figure 7 It can be seen that the capacity decay of the battery in the first few cycles is relatively serious, which may be related to the internal activation of the battery; in the subsequent cycles, the capacity decay is very slow, and there is still an 80% capacity retention rate after 846 cycles.

[0200] The negative electrode material preparation conditions and sodium ion battery assembly process of Example 2-21 are the same as those of Example 1, except that different hard carbon precursors are used. See Table 2 for details.

[0201] Table 2 Comparison of hard carbon negative electrode performance prepared from different hard carbon precursors

[0202]

[0203]

[0204] As can be seen from Table 2, the composite hard carbon prepared with melamine as the hard carbon precursor has the best performance.

[0205] The negative electrode material preparation conditions and sodium ion battery assembly process of Examples 22-34 are the same as those of Example 1, except that different soft carbon precursors are used. See Table 3 for details.

[0206] Table 3 Comparison of hard carbon anode performance prepared from different soft carbon precursors

[0207]

[0208]

[0209] It can be seen from Table 3 that the composite hard carbon prepared using the mesophase pitch as a soft carbon precursor has the best performance.

[0210] The negative electrode material preparation conditions and sodium ion battery assembly process of Examples 35-63 are the same as those of Example 1, except that the doping types and impurity source precursors are different, see Table 4 for details.

[0211] Table 4 Comparison of hard carbon negative electrode performance prepared by different doping types and impurity precursors

[0212]

[0213]

[0214] It can be seen from Table 4 that phosphoric acid doping has the best effect and the prepared hard carbon negative electrode has the best performance.

[0215] The negative electrode material preparation process and sodium ion battery assembly process of Examples 64-92 are the same as those of Example 1, except for the different pre-carbonization temperatures and times, that is, the temperatures and times of the first sintering. See Table 5 for details.

[0216] Table 5 Comparison of hard carbon negative electrode performance prepared at different pre-carbonization temperatures and times

[0217]

[0218]

[0219] It can be seen from Table 5 that the pre-carbonization temperature and time parameters below 1000°C have little effect on the performance of the final synthesized composite hard carbon negative electrode; after the temperature exceeds 1000°C, the pre-carbonization temperature and time have a very obvious effect on the performance. Preferably, the hard carbon prepared by calcining at 700°C for 5 hours has the best performance.

[0220] The negative electrode material preparation process and sodium ion battery assembly process of Examples 93-103 are the same as those of Example 1, except that different pore-forming agents are used. See Table 6 for details.

[0221] Table 6 Comparison of hard carbon negative electrode performance prepared using different pore-forming agents

[0222]

[0223]

[0224] It can be seen from Table 6 that the type of pore former has a great influence on the electrochemical performance of the composite hard carbon negative electrode, especially on the capacity, mainly because the type of pore former directly determines the pore structure of the composite hard carbon material. Preferably, the composite hard carbon prepared using potassium hydroxide pore former has the best performance.

[0225] The negative electrode material preparation process and sodium ion battery assembly process of Examples 104-108 are the same as those of Example 1, except for the different mass ratios of the pore formers, as shown in Table 7 for details.

[0226] Table 7 Comparison of hard carbon negative electrode performance prepared with different pore-forming agent mass ratios

[0227]

[0228] It can be seen from Table 7 that the content of the pore former has a great influence on the electrochemical properties of the composite hard carbon negative electrode. Excessive pore former will lead to excessive pore formation, and the pore structure with inappropriate size cannot achieve sodium storage. Preferably, the composite hard carbon negative electrode prepared at a mass ratio of 1:1 has the best performance.

[0229] The negative electrode material preparation process and sodium ion battery assembly process of Examples 109-127 are the same as those of Example 1, except for the different pore-forming temperatures and times, i.e., the temperature and time of the second sintering. See Table 8 for details.

[0230] Table 8 Comparison of hard carbon negative electrode performance prepared at different pore-forming temperatures and times

[0231]

[0232]

[0233] It can be seen from Table 8 that the pore-forming temperature and time have a great influence on the electrochemical properties of the composite hard carbon negative electrode, and the pore-forming parameters directly affect the structure of the pores; preferably, the composite hard carbon negative electrode prepared by calcining at 700°C for 3 hours has the best performance.

[0234] The negative electrode material preparation process and sodium ion battery assembly process of Examples 128-151 are the same as those of Example 1, except that the soft carbon coating is set at different temperatures and times, see Table 9 for details.

[0235] Table 9 Comparison of hard carbon anode performance prepared at different temperatures and times for soft carbon coating

[0236]

[0237]

[0238] It can be seen from Table 9 that the temperature and time parameters set in the soft carbon coating step have a great influence on the electrochemical performance of the composite hard carbon negative electrode. The main reasons include two: the carbonization effect of the soft carbon precursor is different when calcined at different temperatures and for different times; medium-temperature calcination will change the carbon layer structure, defects and pore structure of the hard carbon. Preferably, the composite hard carbon negative electrode prepared by calcining at 1300°C for 4 hours has the best performance.

[0239] The negative electrode material preparation process and sodium ion battery assembly process of Examples 152-159 are the same as those of Example 1, except that different dispersants are used in the entire preparation process. For details, see Table 10.

[0240] Table 10 Comparison of hard carbon negative electrode performance prepared using different dispersants

[0241]

[0242]

[0243] It can be seen from Table 10 that the dispersant used in the preparation of the composite hard carbon negative electrode has little effect on the overall performance, and the dispersant is mainly used for uniform mixing of different components; preferably, ethanol is the best dispersant screened out.

[0244] The composite hard carbon material prepared by the present invention, when used as the negative electrode material of a sodium ion battery, has low raw material cost and no pollution, and the specific capacity, cycle performance and first coulomb efficiency of the obtained negative electrode material are all improved, and can be used for the negative electrode of a high-performance sodium ion battery. The emergence of sodium ion batteries not only alleviates the problem of limited lithium ion resources and high costs, but also has simple positive and negative electrode materials, cheap and easy to obtain, environmentally friendly and safe, simple production process and low cost, and is a sodium ion battery with high specific capacity, high cycle performance and high safety.

[0245] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A composite hard carbon material, characterized in that: The composite hard carbon material comprises: A hard carbon particle matrix, wherein doping active sites and pores are dispersed in the hard carbon particle matrix, one end of the pores extends into the interior of the hard carbon particle matrix, and the other end is distributed on the surface of the hard carbon particle matrix to form an opening; A soft carbon layer is coated on the surface of the hard carbon particle matrix and covers the opening; The pores have a pore size range of 0.6 nm to 5 um, and the pores have a semi-enclosed structure. The pores are multi-level micro-nano pores, including both nano-scale pores and micro-scale pores. The composite hard carbon material is prepared by the following steps: S1: dispersing a hard carbon precursor in a dispersant, adding a doping precursor and mixing, and evaporating to dryness to obtain a mixed system of the doping precursor and the hard carbon precursor; S2: sintering the product of step S1 for the first time in a protective atmosphere to obtain pre-carbonized carbon; S3: mixing the pre-carbonized carbon with a pore-forming agent, and then sintering the mixture for a second time to obtain porous carbon; S4: adding a soft carbon precursor to the porous carbon and performing a third sintering to obtain the composite hard carbon material.

2. The composite hard carbon material according to claim 1, characterized in that The doped active sites include at least one of nitrogen doped active sites, phosphorus doped active sites, sulfur doped active sites, oxygen doped active sites and boron doped active sites.

3. The composite hard carbon material according to claim 1, characterized in that: The raw materials for preparing the composite hard carbon material include a hard carbon precursor, a dispersant, a doping precursor, a pore former and a soft carbon precursor.

4. The composite hard carbon material according to claim 3, characterized in that: In the preparation raw materials, the addition amount of the soft carbon precursor is 20% to 400% of the hard carbon precursor in terms of mass percentage. 5 . The composite hard carbon material according to claim 3 , wherein the hard carbon precursor comprises at least one of a triazole precursor, a resin precursor, sugar, starch, gelatin, phloroglucinol and an aniline precursor. 6 . The composite hard carbon material according to claim 3 , wherein the doping precursor comprises at least one of a phosphorus-containing precursor, a sulfur-containing precursor, and a nitrogen-containing precursor. 7 . The composite hard carbon material according to claim 3 , wherein the pore former comprises at least one of a chemical pore former and a physical pore former. 8 . The composite hard carbon material according to claim 3 , wherein the soft carbon precursor comprises at least one of a petrochemical soft carbon precursor and a coal chemical soft carbon precursor.

9. The composite hard carbon material according to claim 1, characterized in that: In step S2, the temperature of the first sintering is 300°C to 1600°C.

10. The composite hard carbon material according to claim 1, characterized in that In step S3, the temperature of the second sintering is 400°C to 1600°C.

11. The composite hard carbon material according to claim 1, characterized in that: In step S3, the amount of the pore former added is 30% to 400% of the mass of the pre-carbonized carbon.

12. The composite hard carbon material according to claim 1, characterized in that In step S4, the temperature of the third sintering is 600°C to 2200°C.

13. A negative electrode material for a sodium ion battery, characterized in that: The composite hard carbon material comprises the composite hard carbon material according to any one of claims 1 to 12.

14. A sodium ion battery, characterized in that: Including the sodium ion battery negative electrode material as described in claim 13.

Citation Information

Patent Citations

  • Biomass-based sodium ion battery hard carbon anode material, and preparation method and application thereof

    CN110719891A

  • Hard carbon negative electrode material for lithium ion secondary battery and preparation method of hard carbon negative electrode material

    CN113113601A

  • Preparation method of hard carbon negative electrode for high-energy-density sodium ion battery

    CN114335523A